Efek jumlah kehilangan gigi posterior terhadap bentuk kondilus di rsgm-p fkg usakti melalui radiografi panoramik (Laporan Penelitian) - Maria Resita Octavia; M. Novo Perwira Lubis (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Effects of tooth loss is the cause of occlusal imbalance that can cause changes in the shape of the condyle, which usually occurs after the age of 30 years. The condyle shapes were classified into 6 types; normal, osteophyte, flattening, erosion, subcortical cyst, and sclerosis. Objective: Determine whether there is an effect of the number of posterior tooth loss on the condyle shape in adult aged 30-45 years using panoramic radiography at Radiology Installation of the RSGM-P FoD, Trisakti University. Research method: Cross-sectional approach to the condyle shape from 80 panoramic radiograph samples with the number of tooth loss <3 and ≥3 posterior teeth at Radiology Installation of the RSGM-P FoD, Trisakti University with subjects aged 30-45 years. Result: In the number of posterior tooth loss <3 teeth and ≥ 3 teeth on the right and left sides, the condyle shapes are generally normal. There are pathological shapes that is most found is flattening and the least found is osteophyte. No subcortical cyst was found. Condylar process which undergoes more changes is on the left side and the prevalence in women is higher. The research data was analysed using Chi-square test with the result p > 0.05. Conclusion: There is no significant effect between the number of posterior tooth loss on the condyle shape in adult subject aged 30-45 years using panoramic radiography at the Radiology Installation of the RSGM-P FoD, Trisakti University.